VEGETATION STRUCTURE AND DIVERSITY OF URBAN PARKS AND GARDENS IN BENIN CITY, EDO STATE, NIGERIA - Aigbobo, E. N.; Oyerinde, O. V.; Olusola, J. A.; Adeduntan, S. A. (Journal of Science, Technology and Innovation Research, 2026)
The diversity and species richness of parks and gardens were assessed in the urban axis of Benin City. Ogba Zoological Garden and Nature Park and the Benin Golf Course were selected for the study. Random sampling inventory was used to carry out field inventory, tree heights and diameter at breast height (Dbh) were measured at the sites. The relative density, dominance, important value index (IVI), species richness, evenness and diversity were also estimated. The results showed that Ogba Zoological Garden comprised of 244 trees/ha with a species composition of 50 and distributed into 23 families and has diversity index of 3.72 respectively. Benin Golf Course, had a population estimate of 77 trees/ha comprising of 15 species distributed into 9 families and with a diversity index of 2.12. Although, the diversity index was high for both parks, Ogba Zoo had some threatened species with important value index greater than one. Therefore, conservation efforts should be geared towards protecting those species.